Долговременная повреждаемость трансверсально-изотропных композитных материалов при дробно-степенной функции долговечности - Назаренко, Л.B. (Видавничий дім "Академперіодика" НАН України, 2008)
The theory of long-term damageability is generalized to the case of a discretely fibrous composite with stochastic structure. The appearance of damages in the composite is modeled by the formation of stochastically positioned micropores. The algorithms of calculation of the temporal dependences of macrostresses, macrodeformations, and the microdamageability of components of a granular material are constructed, and the relevant curves in the case of a fractional power function describing the durability are obtained.